Critical barriers and countermeasures to urban regeneration from the stakeholder perspective: a literature review - Liao, Zhiwei; Liu, Menglan (Frontiers in Sustainable Cities, 2023)
Urban renewal involves a wide range of stakeholders with diverse expectations and interests. Conflicts in urban renewal projects arise from intricate relationships among multiple stakeholders, hindering the urban renewal process. With a large amount of current literature examining the barriers, difficulties, and solutions in urban regeneration, a critical review is required to holistically summarize these main concerns and challenges from the stakeholder perspective. Based on 347 journal papers collected from the Web of Science core database, this study investigates the development, trajectory, and tendency of prior studies through a bibliometric analysis. Then, a critical review is documented with eight critical barriers in the economic and social aspects from the stakeholder perspective. To address these issues, this study proposes a strategic framework for value creation, collaborative governance, and benefit sharing. Accordingly, future research agendas are also presented. This study could provide researchers with a systematic understanding of the critical barriers and potential strategies in urban regeneration fields.